ONO‐7684 a novel oral FXIa inhibitor: Safety, tolerability, pharmacokinetics and pharmacodynamics in a first‐in‐human study. Issue 8 (23rd January 2021) - Beale, Dominic; Dennison, Jeremy; Boyce, Malcolm; Mazzo, Francesca; Honda, Naoki; Smith, Paul; Bruce, Mark
Abstract : Aims: The objectives of this study were to investigate the safety, tolerability, pharmacokinetics and pharmacodynamics of single and multiple oral doses of ONO‐7684, a novel activated factor XI (FXIa) inhibitor, in healthy subjects. Methods: This was a first‐in‐human (FIH), randomised, placebo‐controlled, double‐blind, single and multiple dose study in healthy subjects under fed and fasted conditions. This study consisted of two parts: single ascending dose (Part A; 1, 5, 20, 80, 150 or 300 mg ONO‐7684 or placebo) and multiple ascending doses (Part B; 80, 150 or 250 mg ONO‐7684 or placebo daily for 14 days). In both parts, subjects were randomised in a 3:1 ratio to receive ONO‐7684 or placebo. Results: ONO‐7684 was well tolerated at all dose levels tested following both single and repeated doses, with a low overall incidence of treatment‐emergent adverse events. There was no evidence to suggest a bleeding risk. Dose proportionality in exposure was observed for the range of 1–300 mg ONO‐7684 in Part A. In Part A, the half‐life of ONO‐7684 administered in the fasted state ranged from 16.0 to 19.8 hours. In Part B, the half‐life of ONO‐7684 administered in the fed state ranged from 22.1 to 27.9 hours, supporting once daily oral dosing. ONO‐7684 strongly inhibited factor XI coagulation activity (FXI:C) and increased activated partial thromboplastin time (aPTT), with a mean maximum on treatment percentage inhibition versus baseline of 92% and a mean maximum on treatment ratio‐to‐baseline of 2.78, respectively, at 250 mg ONO‐7684 daily. Conclusions: The data generated in this FIH study demonstrate the promising potential of oral FXIa inhibition and ONO‐7684 for indications requiring anticoagulation.